The Combination Diagnostic Test for Tuberculosis Screening in HIV Patients in Referral Hospitals in Indonesia - Murtiani, Farida; Rosamarlina, Rosamarlina; Purnama, Asep; Farhanah, Nur; Utama, Made Susila; Agustin, Heidy; Sarif, Armaji Kamaludi; Widiantari, Aninda Dinar; Hasugian, Armedy Ronny (Public Health of Indonesia, 2025)
Background: Screening tests are needed to help screen suspected Tuberculosis (TB) pulmonary with HIV positive. With the limitation of specificity of the screening test and the need for combination with laboratory tools to increase that, a combination with standard examination is still needed, especially for limited healthcare facilities. Objective: This study aimed to determine Pulmonary TB screening tests with Human Immunodeficiency Syndrome (HIV) positive. Method: This observational study with a cross-sectional design was conducted in four government hospitals. Study subjects were inpatients and outpatients who met study inclusion criteria (> 14 years of age, HIV positive based on HIV test results, had clinical symptoms of episodic history of fever, and volunteered to take part in the study). Total subjects were 193 people, with episodic history of fever from <24 hours to 120 hours. Result: This study assessed a subject's clinical manifestation, physical examination and X-ray test. The “Night Sweat”, Infiltrates in the Upper Lobe”, “Enlargement of Lymph Nodes and “Left Rhonchi” and their combination have a sensitivity of>85%. Still, only the complete combination has a specificity of> 70%. The combination of “Night Sweat + Enlargement of Lymph Nodes + Left Rhonchi + Infiltrates in the Upper Lobe” and then “Enlargement of Lymph Nodes + Left Rhonchi + Infiltrates in the Upper Lobe” can be an alternative for screening Pulmonary TB-HIV positive with history of fever. Conclusion: Pulmonary TB screening in HIV patients with a history of fever can be used by completely combining clinical manifestation, physical examination, and X-ray. the variables "Night Sweat, Enlarged Lymph Nodes, left rhonchi breath sounds and pulmonary upper lobe infiltrates" in a gradual manner. Keywords: Diagnostic Combination Test; HIV-Tb Coinfection; Tuberculosis Screening; Clinical Manifestations in TB-HIV; Pulmonary TB in HIV Patients